Boride coatings on steel using shielded metal arc welding electrode: Microstructure and hardness - Eroglu, Mehmet (Elsevier Science Sa, 2009)
In the present study, shielded metal arc welding electrodes were produced for making boride coatings and low-carbon steel plates were surfaced with single-pass bead on-plate welds. The effects of the boron content in the electrode shield on the microstructure and hardness of the coatings were investigated. After deposition, microstructural analyses including metallographic examination, wavelength-dispersive X-ray (WDX), X-ray and microhardness measurements of the coatings were evaluated. From the results, it was seen that different boron contents formed primary and eutectic Fe2B, and consequently had an effect on the hardness of the coating. As the amount of boron which was transferred from the electrode shield to the coating increased, the microstructure of the coating changed from the eutectic structure (alpha-Fe+F2B) to primary Fe2B with the eutectic of Fe2B plus martensite, and the hardness increased. The present study has therefore shown that the shielded metal arc welding electrodes produced here for the first time can be used effectively and economically to produce boride coatings on SAE 1020 steel. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Boriding; Fe2B; Hardness; SMAW surfacing